Analysis of polychlorinated biphenyls, polycyclic aromatic hydrocarbons and organochlorine pesticides in the tissues of green sea turtles, Chelonia mydas, (Linnaeus, 1758) from the eastern coast of the United Arab Emirates. (November 2020) - Yaghmour, Fadi; Samara, Fatin; Alam, Isra
Abstract: The level of contamination of selected priority pollutants consisting of polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs) and organochlorine pesticides (OCPs) were investigated from the tissues of stranded green sea turtles, Chelonia mydas, from the Gulf of Oman coast of the United Arab Emirates. Tissue samples - muscle and liver - were collected from 22 stranded green sea turtles from the coasts of Kalba and Khorfakkan from 2016 to 2018. Overall, we detected persistent organic pollutants (POPs) in 77% of the turtles. PAH's were the most frequently detected followed by high concentrations of OCP's (71% and 25% of the turtles, respectively). PCB's were not detected in any samples. Factors such as specimen size, mass of debris ingested and toxin hydrophobicity were not important factors affecting the concentrations of these compounds. Graphical abstract: Unlabelled Image Highlights: Strandings were used to assess the concentration of persistent organic pollutants (POPs) in green sea turtles from the eastern coast of the UAE. POPs were detected in 77.3% of green sea turtle specimens. Of the POPs groups examined ∑OCPs had the highest concentrations and ∑PAHs were the most ubiquitous while all PCBs were below detection PAH exposure is primarily from petrogenic sources with few pyrogenic sources When detected, OCP levels were within or above the range of FAO/WHO maximum safety levels of food products